Moderate exercise prevents functional remodeling of the anterior pituitary gland in diet-induced insulin resistance in rats: Role of oxidative stress and autophagy - Mercau, María Elisa (2016)
A sustained elevation of glucocorticoid production, associated with the establishment of insulin resistance (IR) could addto the deleterious effects of the IR state. The aimofthis study is to analyze the consequences of long-term feeding with a sucrose-rich diet (SRD) on Pomc/ACTH production, define the underlying cellular processes, and determine the effects of moderate exercise (ME) on these parameters. Animals fedastandard chow withorwithout 30% sucrose in the drinking water were subjected to ME. Circulating hormone levels were determined, and pituitary tissues were processed and analyzed by immunobloting and quantitative real-time PCR. Parameters of oxidative stress (OxS), endoplasmic reticulum stress, and autophagy were also determined. Rats fed SRD developed a decrease in pituitary Pomc/ACTH expression levels, increased expression of antioxidant enzymes, and induction of endoplasmic reticulum stress and autophagy. ME prevented pituitary dysfunction as well as induction of antioxidant enzymes and autophagy. Reporter assays were performed in AtT-20 corticotroph cells incubated in the presence of palmitic acid. Pomc transcription was in hibited by palmitic acid-dependent induction of OxS and autophagy, as judged by the effect of activators and inhibitors of both processes. Long-term feeding with SRD triggers the generation of OxS and autophagy in the pituitary gland, which could lead to a decline in Pomc/ACTH/glucocorticoid production. These effects could be attributed to an increase in fatty acids availability to the pituitary gland. ME was able to prevent these alterations, suggesting additional beneficial effects of ME as a therapeutic strategy in the management of IR.